Patient Comorbidities Drive High Mortality Rates Associated with Major Liver Resections Irrespective of Hospital Volume. Issue 7 (July 2021) - Diggs, Laurence P.; Aversa, John G.; Wiemken, Timothy L.; Martin, Sean P.; Drake, Justin A.; Ruff, Samantha M.; Wach, Michael M.; Brown, Zachary J.; Blakely, Andrew M.; Davis, Jeremy L.; Luu, Carrie; Hernandez, Jonathan M.
Introduction: Major hepatectomies are utilized to manage primary hepatic malignancies. Reports from high-volume centers (HVCs) with minimal perioperative mortality focus on multiple aspects of perioperative care, although patient-specific factors remain unelucidated. We identified patient factors associated with outcomes and examined whether these contribute to survival differences. Methods: We queried the National Cancer Database (2006-2015) for patients with primary liver malignancies managed with major hepatectomy. Facilities were dichotomized by volume (high volume: >15 hepatectomies/year). Perioperative outcomes were compared based on patient demographic and clinical characteristics as well as center volume. Results: 4263 patients were included with 78.5% receiving care in low-volume centers (LVCs). 90-day postoperative mortality was higher in LVCs vs. HVCs (12% vs. 7.5%; P < .001). Factors associated with undergoing surgery in LVCs included: living in areas with lower income ( P = .006) and education ( P < .001), having nonprivate insurance ( P < .001), residing near the care center ( P < .001), and having a comorbidity score (CDS) >1 ( P = .014). Patients with CDS ≤ 1 had higher 90-day mortality in LVCs (11.3% vs. 6.6%; P < .001) and had similar outcomes in LVCs and HVCs (15.6% vs. 13.7% P = .6). Patients with CDS > 1 were more likely to receive care in LVCs (16.3% vs. 12.7%; P < .001). Conclusion: Reduced perioperative mortality following major hepatectomy in HVCs is driven by optimal management of patients with low CDS. However, nearly 1 in 5 patients who undergo major hepatectomies have a high CDS and approximately 15% of them succumb in the perioperative period irrespective of the treating centers' experience.